Application programme interface to deductive database - Čaplinskas, Albertas; Milašauskas, Mindaugas (Lietuvos matematikos rinkinys, 1999)
The paper discusses midleware that implements application programme interface to deductive database. New approach is proposed how to implement the application programme interface of such kind.